Nghiên cứu về mặt hóa học một số loài thuộc họ Piperaceae - Nguyễn, Xuân Dũng (Đại học Quốc gia Hà Nội, 2020)
The chemical composition of Piperaceae Species have been investigated, many chemical constituents belonging to different classes of bioactive compounds are found.